Enhancing Customer Satisfaction and Loyalty through Customer-Defined Market Orientation and Customer Inspiration: A Critical Literature Review - R. Khan, Mustafa; M. Ghouri, Arsalan (International Business Education Journal, 2018)
The aim of this paper is to conceptualize the significance of customer-defined market orientation in creating superior customer value and building long-term customer relationship which in turn increases the customer satisfaction and loyalty, moreover, the framework also theorized the mediating role of customer inspiration to strengthen the framework. A comprehensive review of latest conceptual and empirical literature was grounded to develop the propositions. Teachers and students of higher education institution shall be taken as a social lab for examining the propositions, and to report the empirical findings. The finding of this study provides a basis for developing a model to obtain customer satisfaction and loyalty. This study could be of practical value for organizations who want to improve satisfaction and loyalty among their customers, with a special focus on teachers and students since they are considered as a potential cluster of the market. This paper makes a significant contribution by developing a conceptual framework to improve customer satisfaction and customer loyalty through customer inspiration and customer-defined market orientation practices.